2021
DOI: 10.1080/15715124.2021.1885421
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the ecological functions of the Litani River Basin, Lebanon

Abstract: Although Lebanon has the highest mean annual rainfall of all Middle Eastern countries, it is affected by water stress, negatively impacting agricultural food production, energy generation, and public health. The Bekaa Plain, where the Litani River Basin (LRB) is located, suffers serious water quality and quantity problems, which threaten agricultural productivity and public health. Most of the domestic and industrial water in the basin is left untreated. This study investigates prevailing water management issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Notably, the Litani River is the chief source of irrigation for agricultural lands in the Beqaa Valley and the South, and it has been well established that the river is being subjected to different pollutants, including pesticides and human and animal waste [73,74]. For example,~69 villages and cities release approximately 47 Mm 3 per year of raw sewage into the Litani River [75]. Taken together, it appears that a high number of water samples from agriculturally important rivers in Lebanon were fecally contaminated and were deemed unacceptable for irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Litani River is the chief source of irrigation for agricultural lands in the Beqaa Valley and the South, and it has been well established that the river is being subjected to different pollutants, including pesticides and human and animal waste [73,74]. For example,~69 villages and cities release approximately 47 Mm 3 per year of raw sewage into the Litani River [75]. Taken together, it appears that a high number of water samples from agriculturally important rivers in Lebanon were fecally contaminated and were deemed unacceptable for irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 below depicts potential pathways [ 64 ] by which resource nexus projects can impinge on the health of humans [ 65 ] biodiversity [ 66 ], and natural ecosystems [ 67 ] as well as impact on determinants of health [ 60 , 68 ] through disrupting the ecosystem services of provisioning, regulating, supporting, and preserving culture [ 64 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our review identified numerous ways that water, energy, and land insecurities drive disparities in the determinants of health for human wellbeing and ecosystems [ 58 , 60 , 66 68 , 72 ], particularly, in rural, remote, and Indigenous contexts where the use and extraction of natural resources [ 57 ] create downstream health inequities. For example, Natcher and Ingram report incidences of higher rates of water, energy, and food (WEF) insecurity in rural and remote communities in Northern Canada, where residents struggle with wide disparities in access to safe drinking water, sanitation services, as well as affordable energy and nutritious food [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of river sediments is becoming more important internationally and in Lebanon, there are 14 rivers, but there are few data concerning the concentration of heavy metals in the sediment of the river (Korfali & Davies, 2005;Nehme et al, 2012;Diaba et al, 2014;Nehmeh et al, 2019;Nehmeh et al, 2020;Darwish et al, 2021). The Litani River is the longest river in Lebanon, with a length of 172 km and largest basin area of about 2180 km 2 .…”
Section: Introductionmentioning
confidence: 99%